Perancangan Sistem Informasi Perpustakaan AMIK STIEKOM Sumatera Utara Berbasis Teknologi Radio Frekuensi Identification (RFID) - Sinaga, Sony Bahagia; Hasugian, Paska Marto (LPPM UNIKA Santo Thomas Medan, 2017)
This study describes the data structure in designing and building an AMIK STIEKOM North Sumatra library information system using Radio Frequency Identification (RFID) based on client servers. The author hopes that readers will better understand the problem solving of parking that is more integrated and well-documented and efficient in its operations. The data structure that has been designed is able to identify the number of participants who have been equipped with Radio Frequency Identification (RFID) library system technology. Students who borrow or return books are selected through application technology in accordance with student data I recorded in the database. Only data on students / I who are registered in the database can borrow and return books to the AMIK STIEKOM North Sumatra library. The process of selecting data in the library system with RFID technology is carried out in three stages, namely the logical design stage, the physical design stage, and the interface design stage.